An evaluation of the phytotoxicity of filter backwash water coagulation products from a pool water system - Łaskawiec, Edyta; Dudziak, Mariusz; Wyczarska-Kokot, Joanna (Oficyna Wydawnicza Politechniki Wrocławskiej, 2018)
The possibility of using the process of coagulation for purifying the filter backwash water from a swimming pool water system has been presented. The assessment of the process efficiency based on the physicochemical parameters was extended by a phytotoxicity analysis of products (sludges and supernatant liquids) obtained from the coagulation processes. The phytotoxicity of sludges was examined with respect to garden cress (Lepidium sativum) and white mustard (Sinapis alba), while duckweed (Lemna minor) was used for studying liquids. Coagulation process was highly effective in purifying backwash water when the lowest of the studied aluminum coagulant doses (from 7 to 20 mg/dm3) was used. Moreover, the phytotoxicity assessment of backwash water allowed the determination of the hazard toward plants, which would be posed by using the backwash water for plant irrigation. The high stimulation of the growth of plant indices, observed in samples with raw backwash water, was caused by nutritive nitrogen and phosphorus. Their removal, in the case of postcoagulation solutions, significantly contributed to the inhibition of plant growth. In turn, sludges derived from both raw washings and coagulation exhibited phytotoxicity.
Environment Protection Engineering. Vol. 44, 2018, nr 4, s. 43-56
Keywords: ochrona środowiska; inżynieria środowiska; czasopisma